Damage evolution characteristics of saw-tooth joint under shear creep condition. (March 2021) - Zhang, Xing; Lin, Hang; Wang, Yixian; Yong, Rui; Zhao, Yanlin; Du, Shigui
The creep characteristics of joint have an important influence on the long-term stability of rock mass engineering such as tunnels and slopes. In this paper, the sawtooth angle α is taken as the variable, five different numerical models of regular sawtooth joints are established using the discrete element numerical method, to study the shear mechanical characteristics of joints under creep condition. In addition, the shear mechanical properties of joints under transient condition are compared to analysis the influence of creep on the mechanical characteristics of joint. The results show that under shear creep condition: (1) Shear displacement of joint increases stepwise with time. At low sawtooth angles, the difference of joint shear displacement with different normal stresses is large. The long-term shear strength of joint is proportional to normal stress and sawtooth angle. (2) The total absorbed energy U and elastic energy U e of the joint both increase as the sawtooth angle α increases. Dissipated energy U d tends to increase first and then decrease with increasing sawtooth angle. Compared with the energy characteristics under transient condition, it is found that the joint under creep condition not only has a lower shear strength, but also requires less total absorbed energy and dissipative energy, and fewer cracks at critical failure. (3) Before the peak strength, the damage variable D increases nonlinearly with the shear displacement. Compared with the transient condition, the damage amount corresponding to the peak strength under the creep condition is smaller, and the evolution rate of the damage variable D with shear displacement at the critical failure is higher.